Limitações urbanas e impactos ambientais decorrentes das feições erosivas lineares identificadas no perímetro urbano do município de São Francisco de Assis/RS - Cardias, Marcia Elena de Mello (2022)
Among environmental problems, erosion is considered a serious problem on a global scale because it causes serious damage to the population and the environment. Even though it is a natural process (repeatedly aggravated by anthropic action). Among the types of erosion we have the gully which constitutes a great destructive power of land leading to the loss of materials by soil erosion. Therefore, this research presents an analysis of the distribution of gullies and their influence on the urban expansion of the municipality of São Francisco de Assis/RS through the study of the analysis of the distribution of gullies near the urban perimeter of the municipality and the characterization of the municipal urbanization process that occurred in 2004 and 2018. This study takes place since the environmental and social problems should not be observed separately and their studies should be aimed at understanding the relationship between society and nature in its entirety. For this work, the methodological proposal of Libault (1971) was used, which is composed of four levels of research, namely: the compilation level stage where the bibliographic survey was carried out on the topic addressed (erosion and its types, classification of erosive processes, climate, vegetation, urbanization, political, economic and social data of the municipality and other concepts relevant to the research), still at this level and with the help of the Google Earth Pro software, the erosive features were identified in the cutout established for the research area and which would be the object of study of the work. Images of the municipality dating from the years 2004 and 2018 were collected in order to later and together with political, economic and social data from São Francisco de Assis/RS to compare the urban expansion of the municipality in these two years.; the correlative and semantic level: at these levels the themes and information about the variables collected in the first level were grouped together in a geographical order with correlations of the same order, so that later the interpretation of the referred variables that gave theoretical support for the progress of the research in the field and also for the construction of the cartographic base used; and finally, the normative level where the analysis of the results was carried out, reaching the conclusion that the existing gullies in the surroundings of the urban fabric of the municipality influence the urban expansion, making clear the need for studies and practices of interventionist public policies together with an environmental education based on technical knowledge aiming to solve the environmental, social and economic problems caused by the advance of erosive features, because its occurrence is relevant in the municipality taking into account the size of its total area. Thus, there is a need to review the type of use and management of soils in the area, as well as the practices and techniques that can be used for the recovery of areas in degradation to occur.